P622 The use of seegene's allplex™MG & AziR assay for the detection of mycoplasma genitalium and macrolide resistance in wales. (14th July 2019) - Barratt, Andrew; Gifford, Laura; Jones, Sophie; Spiller, Owen; Moore, Catherine
Abstract : Background: Mycoplasma genitalium (Mgent) is a sexually transmitted bacteria, associated with cervicitis and pelvic inflammatory disease in women and non-gonococcal urethritis in men. These bacteria lack cell walls and many prokaryotic metabolic pathways, mediating inherent resistance to most antimicrobials. Furthermore, Mgent has garnered concern as the prevalence of both fluroquinolone and macrolide resistance has increased significantly in recent years, further restricting possible therapeutic avenues. In January 2019, Public Health Wales deployed the Seegene Allplex™MG & AziR assay to determine the presence of MG and its susceptibility to macrolides from genitourinary samples. This kit is novel in its ability to not only detected MG, but also define which specific 23S rRNA gene macrolide-resistance mediating mutations (MRM) are present without requirement for sequencing. Methods: 170 clinical samples (collected Jan-March 2019) were investigated: 83 clinical samples submitted from symptomatic patients (suspected MG infections by BASHH guidelines) combined with 87 samples randomly selected from clinical samples submitted for Cobas gonorrhoea/chlamydia (NG/CT) testing (non-targeted). All samples were from patients attending a genitourinary medicine (GUM) clinic in South Wales. Samples were extracted and prepared using the Hamilton Microlab Nimbus, STARMag universal cartridge extraction kit and Allplex™MG & AziR assay. Amplification and detection were performed by a Bio-Rad CFX96 equiped with SeeGene interpretative software. Results: Mgent prevalence with suspected NG/CT patients was 5/87 (5.7%) with 4 (80%) containing MRM (2x A2058G and 2x A2059G), while prevalence within the Mgent-suspected group was 11/83 (13.3%) with 5 (45.5%) containing MRM (4x A2059G and 1x A2058G mutations). Further up-to-date cumulative data to be presented at IUSTI. Conclusion: Mgent prevalence was 5.7% in the non-targeted cohort, while targeted patients gave 13.3% prevalence for a South Wales GUM clinic. Macrolide resistance prevalence was 56% on average. These results justify the implementation of routine Mgent and macrolide resistance testing in South Wales, abiding by European and BASHH guidelines. Disclosure: No significant relationships.